2018
DOI: 10.18608/jla.2018.53.7
|View full text |Cite
|
Sign up to set email alerts
|

Gaze-Driven Design Insights to Amplify Debugging Skills: A Learner-Centered Analysis Approach

Abstract: This study investigates how multimodal user-generated data can be used to reinforce learner reflection, improve teaching practices, and close the learning analytics loop. In particular, the aim of the study is to utilize user gaze and action-based data to examine the role of a mirroring tool (i.e., Exercise View in Eclipse) in orchestrating basic behavioural regulation during debugging. The results demonstrated that students who processed the information presented in the Exercise View and acted upon it, improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Further, each data stream carries a different set of noise sources, and hence, improving the signal-to-noise-ratio for each data stream and having it at similar levels might be a tedious task (Sharma, Papamitsiou, et al ., 2019 ). In addition, each data stream entails a separate type of features and measures (emotions from faces, D'Mello & Graesser, 2012 ; attention from eye-tracking, Mangaroska, Sharma, Giannakos, Traeteberg, & Dillenbourg, 2018 ; mental workload from EEG, Doppelmayr, Klimesch, Schwaiger, Auinger, & Winkler, 1998 ), and once the different measures and features are extracted from the collected, cleaned (noise-removal) and synchronized data streams, extracting LA-specific guidelines is another challenge (Bakharia et al ., 2016 ;Giannakos et al ., 2019 ). Given that most researchers on MMLA rely on custom-developed scripts and manual data alignment (Worsley, 2018 ), MMD can be inaccessible to those who are not already invested in this type of research and/or do not have the necessary technical competence.…”
Section: Practitioner Notesmentioning
confidence: 99%
“…Further, each data stream carries a different set of noise sources, and hence, improving the signal-to-noise-ratio for each data stream and having it at similar levels might be a tedious task (Sharma, Papamitsiou, et al ., 2019 ). In addition, each data stream entails a separate type of features and measures (emotions from faces, D'Mello & Graesser, 2012 ; attention from eye-tracking, Mangaroska, Sharma, Giannakos, Traeteberg, & Dillenbourg, 2018 ; mental workload from EEG, Doppelmayr, Klimesch, Schwaiger, Auinger, & Winkler, 1998 ), and once the different measures and features are extracted from the collected, cleaned (noise-removal) and synchronized data streams, extracting LA-specific guidelines is another challenge (Bakharia et al ., 2016 ;Giannakos et al ., 2019 ). Given that most researchers on MMLA rely on custom-developed scripts and manual data alignment (Worsley, 2018 ), MMD can be inaccessible to those who are not already invested in this type of research and/or do not have the necessary technical competence.…”
Section: Practitioner Notesmentioning
confidence: 99%
“…At present, research in MMLA has focused on studying and modelling learning strategies (Mangaroska, Sharma, Giannakos, Traeteberg, & Dillenbourg, 2018;Worsley & Blikstein, 2015), predicting high-level constructs such as learners' attention and engagement (Chan, Ochoa, & Clarke, 2020), building more accurate learner models (Giannakos, Sharma, Pappas, Kostakos, & Velloso, 2019), designing multimodal learning interfaces (Echeverria et al, 2019), or generating new insights into teaching and learning at a more fine-grained level (Martinez-Maldonado et al, 2020;Prieto, Sharma, Kidzinski, Rodríguez-Triana, & Dillenbourg, 2018). In fact, MMLA promises to bridge theory and complex learning behaviour (Worsley, 2014), support educators' role in addressing students' individual needs, expectations, and skills in physical (Ogan, 2019) and digital (Ochoa et al, 2018) learning settings, as well as tackle the complexities of orchestrating (e.g., designing, managing, adapting) learning activities at multiple social levels beyond the challenges (e.g., time, mental effort) instructors face in their everyday practice (Prieto et al, 2018).…”
Section: Multimodal Learning Analytics Researchmentioning
confidence: 99%
“…As described in Section 3.1.2, another frequently used theory in MMLA research is CLT, which is discussed in six papers (see Figure 3). In four of these works, CLT is combined with other theories to account for other cognitive (Mangaroska et al, 2018) aspects of learning as well as the embodiment (Lee‐Cultura et al, 2022) and Papert's notion of constructionism (Papavlasopoulou et al, 2018). All papers focusing on CLT use MMLA with the goal of accessing learners' cognitive capacities (eg, how they process information; Mangaroska et al, 2018) and identifying differences and commonalities between the observed or self‐reported cognition of learners and cognitive‐related MMLA measurements that are unobservable by naked eye, such as CL based on galvanic skin responses (Larmuseau et al, 2020) and CL and arousal (Lee‐Cultura et al, 2022).…”
Section: Resultsmentioning
confidence: 99%